374. Candidemia Management and Associated Clinical Outcomes in Hospitalized Patients: An Opportunity for Antifungal Stewardship. (26th November 2018) - Patel, Saloni; Shulder, Stephanie; Dick, Travis
Abstract: Background: The incidence of candidemia has increased significantly over the past two decades and is a major cause of morbidity and mortality, prolonged hospital stays, and increased healthcare costs. This study aims to evaluate current practices of candidemia management and review associated clinical outcomes to identify potential targets for antifungal stewardship. Methods: A retrospective chart review of all patients with a positive blood culture for Candida spp. between July 2016 and June 2017 was conducted at a large academic medical center. The primary endpoint was time to effective therapy, defined as time from first positive blood culture to start of an antifungal with in vitro susceptibility. Secondary endpoints were time to clearance of candidemia and 30-day all-cause mortality. Data analysis was conducted and reported using descriptive statistics. Results: A total of 36 patients with candidemia were included, a majority of whom were consulted by the Infectious Diseases (ID) team (81%). C. albicans and C. parapsilosis were the most common pathogens (36% and 25%, respectively) and sources of candidemia varied, with the most common being a line-related source (42%). Median time to effective therapy was 0.3 hours (IQR 0.12–9.95). Sixty-four percent of patients received a nonazole, primarily caspofungin, and 36% of patients received an azole as empiric antifungal therapy. Selection of empiric fluconazole was deemed suboptimal for 17% of patients, all of whom received delayed or no ID consult. Significantly more ID consult patients received an ophthalmology consult vs. non-ID consult patients (65% vs. 0%, P = 0.002). Additionally, echocardiograms were more frequent in ID consult vs. non-ID consult patients (52% vs. 29%, P = 0.408). Median time to candidemia clearance was 58 hours (IQR 46.4–95.6) and 30-day all-cause mortality was 25%. Conclusion: Most patients were started on effective antifungal therapy once candidemia was identified. Patients with an ID consult were more likely to receive ophthalmology consults or echocardiograms to rule out optic or cardiac involvement, respectively. Antifungal stewardship efforts geared toward establishment of institutional guidelines, candidemia treatment bundles, or mandatory ID consult may be considered to improve current practices of candidemia management. Disclosures: All authors: No reported disclosures.